Overview of major cutaneous and subcutaneous skin problems in horses and their associated risk factor in and around Bishoftu town - Alemayo Negera; Soressa Bakala; Bikila Abebe (International Journal of Veterinary Science and Research - Peertechz Publications, 2023)
Horses are the most important animals in the packing and transport systems of Ethiopia. Though disease and related problems are significant impediments to their performance, their socioeconomic contribution is frequently undervalued; as a result, their welfare is severely jeopardized. As a result, this cross-sectional study was carried out to identify the major skin problem of working horses in and around Bishoftu town, as well as associated risk factors. A total of 414 working horses were considered for the study. Selected horses were clinically examined for visible skin lesions, and a questionnaire survey was performed simultaneously. The overall prevalence of skin problems was found to be 60%. In decreasing order, the skin problems recorded in the study were wound (41.3%), epizootic lymphangitis (16.4%), and sarcoids (1.9%). There was a significant difference (x2 = 15.66, p 0.05) in the prevalence of wounds among different body condition scores; horses in poor body condition were more exposed to wounds than horses in better body condition. There was a significant difference (p 0.05) in the prevalence of wound up by age group, indicating that horses in their senior years were particularly vulnerable. Injuries caused by an improper harness and saddle design were more prevalent (x2 = 409.93, p = 0.000). A slightly higher proportion of wounds was encountered in the chest area of the body (24%). There was a significant difference (x2 = 4.0028, p 0.05) in the prevalence of epizootic lymphangitis depending on the type of work that indicated that cart horses were more highly affected than pack horses. But there was no significant difference based on age, body condition score, or housing system. There was a significant difference in the prevalence of sarcoids between horses that had been sheltered and those that had not; the non-sheltered horses had a significantly higher prevalence than the sheltered horses. The anatomical distribution of the occurrence of wounds on the horses was found to indicate an association between areas of harnessing, packing, and inappropriate hobbling. This study showed wounds as a major skin problem for working horses in the region. A comprehensive equine health programme should be implemented in order to alleviate the prevailing problem.